2016
DOI: 10.1007/s00276-016-1781-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical risk evaluation of iatrogenic injury to the infrapatellar branch of the saphenous nerve during medial meniscus arthroscopic surgery

Abstract: We defined a common anatomical course for the saphenous nerve and its infrapatellar branches. Then, three different areas were defined at risk for iatrogenic nerve injuries during medial meniscus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…[34] According to many authors, meniscal repair surgery can usually be applied at the following knee positions; varus/valgus stress in slight flexion (10-15°) or at 90-100° of flexion. [34,35] Cuéllar et al [15] in their study, where they measured distances between the suture material used and the peroneal nerve with the knee at 90°, 45°, and 0° of flexion, reported that the 90° of flexion is the safest knee flexion angle for repairing the meniscus. With the flexion of the knee, the posterior neurovascular structures go further away from the meniscal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[34] According to many authors, meniscal repair surgery can usually be applied at the following knee positions; varus/valgus stress in slight flexion (10-15°) or at 90-100° of flexion. [34,35] Cuéllar et al [15] in their study, where they measured distances between the suture material used and the peroneal nerve with the knee at 90°, 45°, and 0° of flexion, reported that the 90° of flexion is the safest knee flexion angle for repairing the meniscus. With the flexion of the knee, the posterior neurovascular structures go further away from the meniscal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty is one of the most performed procedures in the world. However, this procedure, along with anterior cruciate ligament reconstruction, hamstring tendon harvest and medial meniscus surgery can often cause iatrogenic injury to the infrapatellar branch of the saphenous nerve (IPBSN), with rates ranging from 22.2 % to 69 % of patients (Koch et al, 2017;Ochiai et al, 2017;Henry et al, 2018). Furthermore, other procedures such as medial arthroscopic approaches and complementary posteromedial arthrotomies can cause injury to this nerve (Koch et al).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have aimed to assess the position of the IPBSN in order to observe patterns that might indicate a safer space for incision, although it is known that the IPBSN is highly variable (Kerver et al, 2013;Kalthur et al, 2015;Koch et al;Henry et al).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Iatrogenic peripheral nerve damage is a particularly common and devastating clinical entity that leads to significant pain and compromised functional outcomes. 2–4 For example, approximately 5% of patients undergoing arthroscopic hip repair suffer from transient neuropraxia. 5,6 Permanent damage to nerves is a well-known and debilitating health risk associated with peripheral, cranial, and spinal nerve access.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Permanent damage to nerves is a well-known and debilitating health risk associated with peripheral, cranial, and spinal nerve access. 4 In such cases, intraoperative monitoring techniques, primarily involving evoked potentials as well as stimulated and spontaneous electromyography (EMG), provide surgeons with the ability to identify and assess vulnerable nerve sites by probing nerve-muscle activities during surgery. 7–12 Real-time monitoring strategies offer a powerful set of capabilities for surgeons that can positively affect outcomes, but existing intraoperative systems are large, expensive, and cumbersome; they include data acquisition consoles coupled to sensing electrode leads via multiple, fixed electrical connections.…”
Section: Introductionmentioning
confidence: 99%